IMPACT OF EPS ON MARKET PRICES AND MARKET RATIO - Febria Nalurita (Business and Entrepreneurial Review, 2016)
In this paper the researchers have made an attempt to examine the impact of Earnings Per Share on the MarketPrices, Price-Earning-Ratio and Price to Book Value. In the study, the researchers have taken into consideration twenty-four companies which represent Property and Real Estate industry. A reference period of seven years has been taken from 2009 to 2015. In order to achieve the objectives of the study, regression data panel has been employed and the findings put forth by the study affirmed that on the one hand there exists a positive relationship between earnings per share and market price of shares and on the other hand earnings per share does not statistically influence the market ratio. We suggest that investors must consider other factors as well as EPS in order to invest in the security market